2003
DOI: 10.1002/jnr.10839
|View full text |Cite
|
Sign up to set email alerts
|

Genomic structure, cochlear expression, and mutation screening of KCNK6, a candidate gene for DFNA4

Abstract: KCNK6 encodes a tandem pore domain potassium channel, TWIK-2, that maps to chromosome 19. Both STS and linkage maps established KCNK6 as a positional candidate gene for DFNA4, a form of autosomal dominant nonsyndromic hereditary hearing loss. Identification and characterization of Kcnk6 expression within the mammalian cochlea established the gene as a functional candidate for DFNA4. Identification of Twik-2 expression in the mouse cochlea was initially established via RT-PCR assay of cochlear RNA. Subsequent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Consequently, they did not investigate K 2P 6.1i in the vestibular periphery. Mhatre et al, 2004 showed that Kcnk6 mRNA is expressed in the mouse cochlea and that K 2P 6.1i is predominantly in the stria vascularis. We detected K 2P 6.1i in the vestibular transitional cells and in nerve terminals in the vestibular epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, they did not investigate K 2P 6.1i in the vestibular periphery. Mhatre et al, 2004 showed that Kcnk6 mRNA is expressed in the mouse cochlea and that K 2P 6.1i is predominantly in the stria vascularis. We detected K 2P 6.1i in the vestibular transitional cells and in nerve terminals in the vestibular epithelia.…”
Section: Discussionmentioning
confidence: 99%
“…2000; Vale and Sanes 2002), in ion channels (Storey et al . 2002; Mhatre et al . 2004), in transcription factors (Illing et al .…”
mentioning
confidence: 99%
“…Deafness (full or partial) and noise over-stimulation have been shown to lead to plastic changes in the mature central auditory pathways (Syka 2002;Moller 2005). Changes that have been reported following deafness include changes in the tonotopic map (Robertson et al 1989;Rajan et al 1993), in cell size (Sie and Rubel 1992;Dodson et al 1994;Lustig et al 1994;Lesperance et al 1995;Willott and Bross 1996;Moore et al 1997;Niparko and Finger 1997;Araki et al 1998;Edmonds et al 1999;Niparko 1999;Nishiyama et al 2000), changes in synaptic contacts and synapse morphology (Kazee et al 1995;Huchton et al 1997;Ryugo et al 1997;Niparko 1999;Russell and Moore 2002;Lee et al 2003), in neurotransmitters and receptors as well as their release, uptake and binding (Caspary et al 1995;Milbrandt et al 2000;Potashner et al 2000;Vale and Sanes 2002), in ion channels (Storey et al 2002;Mhatre et al 2004), in transcription factors (Illing et al 1999;Illing and Michler 2001;von Hehn et al 2004), in oxygen reactive species (Ohlemiller and Dugan 1999;Shi et al 2002), and in stress response molecules (Myers et al 1992;Billings et al 1995;Verstreken et al 1996;Oh et al 2000;Van Campen et al 2002;…”
mentioning
confidence: 99%
“…TASK-1, TREK-1, TWIK-1, and TWIK-2 expression have been found by RT-PCR and immunolocalization methods in various cochlear structures including sensory and supporting cells of the organ of Corti, spiral ganglion, stria vascularis, Reissner's membrane, inner and outer sulcus cell, and cochlear nucleus. 47,[93][94][95][96] Although no association has yet been made between these genes and heritable hearing loss syndromes, 95 acute toxicity produced by high local anesthetic concentrations may occur through disinhibition of these K 2P channels.…”
Section: K 2p Channels and Local Anesthetic Toxicitymentioning
confidence: 99%